Heuristic faculty course timetabling with student sectioning - Chia-Lih, Bong; Sze, San Nah; Noor Alamshah, Bolhassan; Kang-Leng, Chiew (2017)
This paper studies a real faculty course timetabling problem of Faculty of Computer Science and Information Technology (FCSIT), Uni-versiti Malaysia Sarawak (UNIMAS). FCSIT offers 5 four-year pro-grammes. Each programme has own set of courses but some courses are re-quired by more than one programme. List of courses for each semester of all programmes are planned and suggested by faculty as in course plan but stu-dents are free to select their own course registration. FCSIT has to come out with course timetable with no clashes before semester starts. Current curric-ulum-based timetabling method causes clashes and requires few rounds of adjustment. The aim of this study is to come out with better method than the current curriculum-based timetabling practice. A two-stage heuristic with student sectioning consideration method is proposed to solve the problem by student-based approach. A simulator is developed and tested with real da-tasets from FCSIT. It generates clash-free timetables in shorter time as ad-justment is unnecessary. Results shown that simulator solution performs bet-ter in utilise venue resources by reduced 13.1% unnecessary allocation. On top of that, the simulator is proved to be efficient in solving problem for dif-ferent semesters with changed problem size, different offering courses and different resources given.